2019
DOI: 10.1002/ehf2.12564
|View full text |Cite
|
Sign up to set email alerts
|

A giant mystery in giant cell myocarditis: navigating diagnosis, immunosuppression, and mechanical circulatory support

Abstract: Giant cell myocarditis is a rare but often devastating diagnosis. Advances in cardiac imaging and mechanical circulatory support have led to earlier and more frequent diagnoses and successful management. This disease state has wide variation in acuity of presentation, and consequently, optimal treatment ranging from intensity and type of immunosuppression to mechanical circulatory support is not well defined. The following case describes the management of a patient with an unusual presentation of giant cell my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
10
0
2
Order By: Relevance
“…found that patients with biopsy‐proven inflammatory infiltrate with a diminished coronary reserve due to reduced coronary vasodilator capacity. Fallon et al 12 . showed a histologic image of GCM with a capillary surrounded by the lymphocytic infiltrates, which is also found in our patients ( Figure ).…”
Section: Discussionsupporting
confidence: 86%
“…found that patients with biopsy‐proven inflammatory infiltrate with a diminished coronary reserve due to reduced coronary vasodilator capacity. Fallon et al 12 . showed a histologic image of GCM with a capillary surrounded by the lymphocytic infiltrates, which is also found in our patients ( Figure ).…”
Section: Discussionsupporting
confidence: 86%
“… 2 Choosing the optimal evidence-based immunosuppression regimen for the patients is challenging because there have only been some small case series and observational studies and no randomized clinical trials. 15 In this case, we prescribed only PSL and ciclosporin, not azathioprine. The LV function did not recover.…”
Section: Discussionmentioning
confidence: 94%
“…не отмечено ни одного случая развития ГКМ в трансплантированном сердце [18,19]. Сообщается также о повышенном риске острого отторжения у больных с ГКМ в сравнении с ДКМП (16% vs 5%, р = 0,021), однако 1-, 5-и 10-летняя выживаемость не отличается от таковой при иных причинах ТС (94, 82 и 68% соответственно) [20].…”
Section: Discussionunclassified